Pendampingan Memperlancar Bacaan Huruf Al Quran pada Anak Menggunakan Metode Talaqqi di Msuholla Al Ikhlas - Annisa Nur Adawiya (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Community service activities in the form of assistance to facilitate children's reading of the letters of the Qur'an using the talaqii method in the al-Ikhlas prayer room aims to provide guidance and assistance to children so that they can know the letters of the Qur'an at all. do not know the hijaiyah letters and are able to read the letters of the Koran fluently. This activity was carried out in Hamlet 1, Bangun Sari Baru Village, North Sumatra, which was attended by 9 children in the village. Implementation methods include socialization, coaching and mentoring. Activities are carried out every 5 times in 1 week through a test to read the letters of the Koran with Iqra. The results of this service show that the mentoring activities to facilitate children's reading of the letters of the Qur'an using the talaqqi method at the Al Ikhlas Prayer Room went according to what was planned and expected, such as; 1) for children who don't know the hijaiyah letters at all, then after this activity the children will be able to recognize the hijaiyah letters. 2) for children who already know the letters of the Koran, they are able to read the letters of the Koran that are connected. 3) increasing knowledge of reading letters and the different letters of the Koran as well as increasing children's awareness of how important it is to read the Koran. This service activity is carried out to improve the quality of the young generation in the future who love the Koran and have Islamic morals. The results show that as many as 15% of children have entered volume 6 and 10% have entered volume 2. And as many as 75% of children have entered volume 1.